MENINGKATKAN KINERJA PERUSAHAAN MELALUI KNOWLEDGE MANAGEMENT - Sylvia Sylvia (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2010)
A lot of company which have invesment to in gross to obtain;get the tangible asset of like machine, equipments, and technological, so that can improve the company value; but forget to manage the primal asset owned by each individual in company that is knowledge. Knowledge Management have a purpose to push the company of so that to be applying correct technology, supported by human resource which competence in its area, and happened by the going concern study process in it. This article study to hit the knowledge management.